Overview of COVID-19 Surveillance in Amuntai Selatan Public Health Center - Erna Yulida; Irzal Rakhmadhani; Irvan Maulana; Dessy Vinoricka Andriyana (Lambung Mangkurat, 2022)
The COVID-19 pandemic is occurring worldwide, including in rural and remote areas. Prevention and management of pandemics vary greatly depending on the region’s characteristics. Therefore, it was necessary to analyze COVID-19 cases in rural areas to understand the pattern of COVID-19 spread. We used descriptive epidemiological research with a cross-sectional approach in Amuntai Selatan Public Health Center. We found that the most confirmed cases occurred in women, the productive age group who worked as public servants and underwent self-isolation while exposed. While most death cases occurred in men, 56-60 years old, working as public servants and hospitalized. Public Health Center needs to improve reporting records, especially in comorbid and confirmed patient contact data. The characteristics of COVID-19 that more often affect productive adults and workers should be focused on preventing COVID-19 in the future.